Holocene climate and environmental history of Brurskardstjorni, a lake in the catchment of vre Heimdalsvatn, south-central Norway - Velle, G; Bjune, AE; Larsen, J; Birks, HJB (SPRINGER, 2010)
The Holocene lake history, vegetation history and climate history of Brurskardstjorni, an alpine lake in the Jotunheimen Mountains of south-central Norway, are reconstructed. The reconstructions are based on fossil pollen, plant macrofossils, diatoms, chironomids and sediment characteristics. Subsequent to deglaciation, the lake was formed at about 11,000 cal years BP. A diverse chironomid assemblage quickly colonised the lake, whereas the first diatoms were found about 400 years later. At that time, the lake water was turbid with a high pH. The surrounding soils were immature and unstable and dominated by open pioneer vegetation. Compared to the present, summer temperatures were warmer and there was less winter precipitation. From about 10,000 cal years BP, local organic production increased rapidly and from about 9,500 cal years BP a few macrofossils and a high pollen influx of birch suggest that the tree-line was close to the lake. Pine most likely reached its highest tree-line altitude around 9,000 cal years BP and has receded since that time. From about 5,000 cal years BP, the total amount of trees and shrubs decreased and the landscape became more open, probably due to decreasing temperatures and increasing effective moisture lowering the birch tree-line. Coinciding with a cooling during the last 3,000 years, lake-water pH decreased. There is large incongruence between the Holocene July temperatures inferred from pollen and chironomids. The biological proxies responded to a combined effect of environmental change and biotic interactions. This response is interpreted with reference to taxon-environment relationships in the modern calibration data sets and with reference to the latent structure and ecological demands of the fossil assemblages.